Improving Integrated Mental Health Care Through an Advanced Practice Registered Nurse–Led Program: Challenges and Successes. (May 2023) - Emerson, Margaret R.; Huber, Melanie; Mathews, Therese L.; Kupzyk, Kevin; Walsh, Michael; Walker, Jerry
Integrated and collaborative care delivery models have demonstrated efficacy for the management of psychiatric conditions in the primary care environment, yet organizations struggle with implementation of integrated efforts in clinical practice. Delivering care with a population focus versus face-to-face encounters with individual patients requires financial investment and adjustment in care delivery. We discuss the early implementation process of an advanced practice registered nurse (APRN)–led integrated behavioral health care program, including the challenges, barriers, and successes in the first 9 months of the program (January–September 2021), for an academic institution in the Midwest. A total of 161 Patient Health Questionnaire 9 (PHQ-9) and 162 Generalized Anxiety Disorder (GAD-7) rating scales were completed on 86 patients. The mean PHQ-9 score at the initial visit was 11.3 (moderate depression); after 5 visits, it decreased significantly to 8.6 (mild depression) ( P < .001). The mean GAD-7 score at the initial visit was 10.9 (moderate anxiety); after 5 visits, it decreased significantly to 7.6 (mild anxiety) ( P < .001). A survey completed by 14 primary care physicians 9 months after program launch revealed improvements in satisfaction with collaboration but, most notably, in perception of access to and overall satisfaction with behavioral health consultation/patient care services. Program challenges included adapting the environment to enhance leadership roles for the program and adjusting to virtual availability of psychiatric support. A case example highlights the value of integrated care along with improved depression and anxiety-related outcomes. Next steps should include efforts that capitalize on nursing leadership strengths while also promoting equity among integrated populations.